Agama di Panggung Digital: Fenomena Ulama Selebriti dan Budaya Populer - Selamat Rama Dani; M. Nurul Humaidi (Global Education Journal, 2026)
The phenomenon of celebrity clerics in Indonesia represents a crossroads between traditional religious authority and contemporary popular cultural dynamics. This research aims to explore in depth the socio-religious background of the emergence of celebrity scholars, identify their main forms of activities, compare their positions with conventional scholars, analyze their role in the formation of religious culture, and evaluate their socio-religious contributions in Indonesian Muslim society. Using a qualitative approach with a critical literature study design, this study analyzes the sources from the indexed journals Sinta 1-3 and Scopus Q1-Q3 published in the last decade. Data analysis was carried out through deductive thematic based on the framework of Bourdieu's theory of cultural capital, Stark & Bainbridge's religious economics, and Hjarvard's religious mediatization. The findings suggest that celebrity clerics emerged in response to the democratization of digital information that shifted religious authority from institutional to personal. They operate through the digital media ecosystem by adopting the logic of entertainment without abandoning religious substance, albeit with the consequence of a reduction in the depth of content. Socio-religiously, this phenomenon contributes to the expansion of the reach of da'wah and the reconfiguration of popular Islamic identity in Indonesia, while presenting challenges in the form of religious commodification and fragmentation of ulema authority. The novelty of this research lies in the integrative analytical framework that connects the mediatization of religion, symbolic capital, and popular cultural dynamics in the context of Indonesian Islam.